Development of pH-meter monitoring system using Arduino / Mohd Fadhil Ibrahim - Ibrahim, Mohd Fadhil (2012)
This paperwork presents the complete circuit used to interface a pH-meter using Arduino. The objective of study is to investigate the accuracy of the pH-meter using Arduino as a microcontroller. This project has been implement and simulated using OrCAD Tool v10.5. This pH-meter will be able to be monitored using computer via USB connection. Besides that, this pH-Meter are designed to open source that mean this pH-Meter can be install additional function depend on users requirement. In experimental procedure, this project focused on the accuracy of pH-Meter when tested to specified pH buffer. The pH-meter is tested to 4 difference pH buffer to determine the accuracy of this pH–meter. The result shows that this pH-meter has an accuracy of 97% compare to an average pH meter that is about 99% of error. In conclusion, this pH-meter is very good because the accuracy is above 90%.